Transesterifikasi Biodiesel Dari CPO FFA Tinggi Dengan Katalis ZnO Komersial (Pengaruh Variasi Jumlah Katalis Dan Rasio Mol Minyak : Metanol) - Mahdi, Khafid Ali; Yusnimar, Yusnimar; Helianty, Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Crude palm oil (CPO) has a high free fatty acid concentration can be used as a raw material in the production of crude biodiesel. Recently, ZnO compounds are used as heterogeneous catalysts in the biodiesel production. This research was conducted to produce crude biodiesel from CPO with the effect of variations in the mole ratio of reactants and amount of ZnO catalyst. The process of producing crude biodiesel conducted with two stages, esterification and transesterification reactions. Esterification reaction conditions at a temperature of 65°C, mole ratio of oil : methanol (1: 6, 1:12, and 1:18), and amount of catalyst 1%. Transesterification reaction conditions at a temperature of 65°C were used variation of a mole ratio of oil : methanol (1: 6, 1:12, and 1:18), and amount of catalyst (0.3%, 0.4%, and 0.5%). The highest yield of crude biodiesel obtained 96.18% under the conditions of a temperature of 65 °C, the mole ratio of reactants 1:18 and amount of ZnO catalyst 0.5%. Based on results, the crude biodiesel has a density (40°C) 868 kg/m3, kinematic viscosity (40°C) 5.71 mm2/s, a flash point of 164°C, the acid number of 0.72 mg-KOH/g-biodiesel, saponification numbers 20.83 mg-KOH/g-biodiesel and alkyl ester content of 96.56%. These characteristics of biodiesel are suitable to SNI 04 - 7182- 2006 standard.Key words : crude biodiesel, crude palm oil, esterification, transesterification, ZnO